2018
DOI: 10.1158/1538-7445.am2018-4603
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4603: Clinical application and potential usefulness of targeted next-generation sequencing on resected pancreatic ductal adenocarcinoma

Abstract: Introduction: Pancreatic ductal adenocarcinoma (PDA) carries a dismal prognosis. Virtually all PDA are characterized by mutation of four driver genes: KRAS, TP53, CDKN2A and SMAD4 and a long tail of rarely mutated genes. Application of targeted next-generation sequencing (NGS) has entered clinical routine for colon, lung and other cancers. Among patients with resected PDA, usefulness, applicability and prognostic significance of NGS results are still a matter of debate. Aims: To evaluate: 1) the alterations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Understanding the mechanisms underlying these alterations can help identify potential targets for treating PDAC [10][11][12][13]. Genetic studies utilizing whole-exome and gene expression analyses have identified mutations in four tumor driver genes-KRAS, TP53, SMAD4, and CDKN2A-as molecular fingerprints for PDAC, with KRAS being prevalent in nearly all cases of the disease [14][15][16][17][18][19]. While these key driver mutations influence prognosis, diagnosis, and resistance to chemotherapy, targeting these driver mutations has been challenging [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanisms underlying these alterations can help identify potential targets for treating PDAC [10][11][12][13]. Genetic studies utilizing whole-exome and gene expression analyses have identified mutations in four tumor driver genes-KRAS, TP53, SMAD4, and CDKN2A-as molecular fingerprints for PDAC, with KRAS being prevalent in nearly all cases of the disease [14][15][16][17][18][19]. While these key driver mutations influence prognosis, diagnosis, and resistance to chemotherapy, targeting these driver mutations has been challenging [20][21][22].…”
Section: Introductionmentioning
confidence: 99%